(untitled) (Baghdad Science Journal, 2024)
Yeasts inhabit diverse natural environments, including the honeycombs of wild honeybee colonies residing at different elevations. This study investigates yeast populations in honeycombs located at two sampling sites, Bligo and Sukomulyo, Central Java Province, Indonesia, situated in a montane region at elevations of 131.1 and 676 meters above sea level, respectively. Out of the 40 yeast isolates collected, 12 distinct fingerprints were identified, representing ten strains across four species. Debaryomyces hansenii emerged as the predominant species, accounting for seven of the total strains, and being found at both sampling sites. The remaining species included Priceomyces melissophilus, Cystobasidium minutum, and Meyerozyma guillermondii. Overall, yeast abundance in this study was relatively low. The index of abundances (H’) was higher in Bligo (0.796) compared to Sukomulyo (0.636). These findings suggest that elevation may influence yeast populations within honeycombs, with potential interactions with other factors affecting diversity measures.